Assessment of cortical and trabecular bone changes in two models of post‐traumatic osteoarthritis. Issue 12 (17th July 2015) - Pauly, Hannah M.; Larson, Blair E.; Coatney, Garrett A.; Button, Keith D.; DeCamp, Charlie E.; Fajardo, Ryan S.; Haut, Roger C.; Haut Donahue, Tammy L.
ABSTRACT: Subchondral bone is thought to play a significant role in the initiation and progression of the post‐traumatic osteoarthritis. The goal of this study was to document changes in tibial and femoral subchondral bone that occur as a result of two lapine models of anterior cruciate ligament injury, a modified ACL transection model and a closed‐joint traumatic compressive impact model. Twelve weeks post‐injury bones were scanned via micro‐computed tomography. The subchondral bone of injured limbs from both models showed decreases in bone volume and bone mineral density. Surgical transection animals showed significant bone changes primarily in the medial hemijoint of femurs and tibias, while significant changes were noted in both the medial and lateral hemijoints of both bones for traumatic impact animals. It is believed that subchondral bone changes in the medial hemijoint were likely caused by compromised soft tissue structures seen in both models. Subchondral bone changes in the lateral hemijoint of traumatic impact animals are thought to be due to transmission of the compressive impact force through the joint. The joint‐wide bone changes shown in the traumatic impact model were similar to clinical findings from studies investigating the progression of osteoarthritis in humans. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1835–1845, 2015.